2019
DOI: 10.3390/nu11102548
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kinetics of Choline and Choline Metabolites After A Single Dose of SuperbaBoostTM Krill Oil or Choline Bitartrate in Healthy Volunteers

Abstract: As an essential nutrient, the organic water-soluble compound choline is important for human health. Choline is required for numerous biological processes, including the synthesis of neurotransmitters, and it is an important prerequisite for structural integrity and the functioning of cells. A choline-rich diet provides crucial choline sources, yet additional choline dietary supplements might be needed to fully meet the body’s requirements. Dependent on the structure of choline in different sources, absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Choline bitartrate yielded 3-times higher plasma TMAO AUC and 4.4-times higher plasma TMAO maximum increase from baseline compared to phosphatidylcholine and no choline control, consistent with previous studies demonstrating that excess gut microbial-generated TMA production occurred with choline chloride [5,6]. Further, a recent study comparing choline bitartrate and krill oil containing phosphatidylcholine and omega-3 fatty acids also showed greater TMAO production only with choline bitartrate, but not krill oil [31]. The increase in TMAO concentration with choline bitartrate suggests that the non-ester form without requiring an enzymatic conversion step may be a preferred substrate for the gut microbial conversion to TMA and subsequent hepatic oxidation to TMAO.…”
Section: Discussionsupporting
confidence: 88%
“…Choline bitartrate yielded 3-times higher plasma TMAO AUC and 4.4-times higher plasma TMAO maximum increase from baseline compared to phosphatidylcholine and no choline control, consistent with previous studies demonstrating that excess gut microbial-generated TMA production occurred with choline chloride [5,6]. Further, a recent study comparing choline bitartrate and krill oil containing phosphatidylcholine and omega-3 fatty acids also showed greater TMAO production only with choline bitartrate, but not krill oil [31]. The increase in TMAO concentration with choline bitartrate suggests that the non-ester form without requiring an enzymatic conversion step may be a preferred substrate for the gut microbial conversion to TMA and subsequent hepatic oxidation to TMAO.…”
Section: Discussionsupporting
confidence: 88%
“…Most studies comparing FO and KO have used mixed genders, often with a wide age range, and with no attempt to differentiate responses between genders. For example, in two recent studies, 18 subjects (1:1 male to female ratio) aged 18-65 years were studied by Modinger et al [10], and 36 subjects (men and women) aged 18-70 years were studied by Rundblad et al [30]. Therefore, it is not known whether the present results will be applicable to men and post-menopausal women.…”
Section: Discussionmentioning
confidence: 76%
“…Other biochemical features of KO that might contribute to differences in health outcomes compared with FO include the presence of astaxanthin and choline (as phosphatidylcholine, (PC)). Indeed, a recent study showed that the choline from KO was equally bioavailable to free choline but with a later peak absorption [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that 60% of choline in inorganic salts is lost to conversion to trimethylamine (TMA) by intestinal bacteria (45). On the other hand, choline in the form of PC is considerably less converted to TMA as demonstrated in a single-dose study with krill oil (14), potentially resulting in more efficient delivery of choline.…”
Section: Future Directionsmentioning
confidence: 99%
“…In contrast to fish oil, where the fatty acids are typically present in triglyceride form, krill oil contains fatty acids that are largely present in phosphatidylcholine (PC) form ( 13 ). With a high phospholipid content (≥56%), of which PC makes up around 90%, supplementation with 1 g of Superba Boost ™ results in a choline dose of ~70–80 mg. A recent single-dose plasma kinetic study in humans showed that krill oil is an adequate source of choline ( 14 ). In comparison to choline bitartrate, plasma choline levels were similar, but the metabolites betaine and dimethylglycine (DMG) were significantly higher in the krill oil group, and trimethylamine N-oxide (TMAO) levels significantly lower.…”
Section: Introductionmentioning
confidence: 99%